PENGARUH MOTIVASI PELAYANAN PUBLIK TERHADAP SIKAP PEKERJA DAN KECOCOKAN NILAI-NILAI INDIVIDU DENGAN ORGANISASI SEBAGAI PEMEDIASI (STUDI PADA KARYAWAN RUMAH SAKIT UMUM DAERAH DR ZAINOEL ABIDIN BANDA ACEH) - M. Narendra Adha, Nashrillah (Departemen Manajemen, 2017)
This aims of this study is to determine the effect on employee motivation of public service general hospital in Dr. Zainoel Abidin Banda Aceh on the attitudes of workers to match the values of the individual and the organization as a mediating variable. Empirical studies conducted in a public hospital employee Dr. Zainoel Abidin Banda Aceh using a questionnaire as an instrument of research, which sampled in this study is equal to 93 medical and non-medical personnel who are employees of public hospitals dr Zainoel Abidin Banda Aceh. Probability sampling is used as a sampling technique. The data was collected by questionnaire. Methods Hierarchical Linear Modeling (HLM) was used as tools of data analysis using SPSS software. The results of this study indicate that the motivation of public service has significant effect on worker attitudes, motivation of public services significantly influence the suitability of individual values with the organization, the suitability of individual values with the organization significant effect on worker attitudes and in addition obtained results that match the values individuals with partially mediate the organization of public service motivation influence on the attitudes of workers.Keywords : motivation of public service, labor's attitude, and compatibility values individuals with the organization.